ENGLISH FOR BUSINESS PURPOSES SUBJECT: ANALISIS KEBUTUHAN (WANTS) DARI SUDUT PANDANG MAHASISWA PENDIDIKAN BAHASA INGGRIS - Mayuasti Mayuasti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Need analysis is the first stage in developing Specific English courses. The purpose of the analysis is to guarantee the learning process relate with students’ needs and wants. The reason of the importance of the analysis leads this research to investigate Learning Situational Analysis for college students who join in English for Business Subject. It is survey research. The technique in determining sample is purposive. Moreover, the instrument used is the questionnaire. The result of the data is analyzed by statistic formula. The analysis of the data exposes students’ intentions in learning English for business, the chosen strategy for learning, the priority language skill to achieve, the most conducive and effective learning environment to have, and the availability of material and field study opportunity to practice.